Model Transformasi Model Pembelajaran IPS dalam Mengikuti Dinamika Kurikulum - Tri Agustina, Anggia; Della Rahmadani, Nafa; Utami Leviantia, Banja (Jurnal Gentala Pendidikan Dasar, 2023)
Social Sciences (IPS) learning in elementary schools (SD) has a crucial role in shaping students' understanding of the social and cultural realities around them. This research aims to explore and improve social studies learning in elementary schools through the application of innovative learning models. The experimental research method was used involving two groups, namely a control group that took part in conventional learning and an experimental group that applied a project-based social studies learning model. The research results show that the application of the project-based learning model significantly increases students' interest and understanding of social studies material. Analysis of learning achievement data also showed a significant increase in the experimental group compared to the control group. The discussion involves an in-depth analysis of the suitability of the learning model with the social studies curriculum in elementary school and its impact on student motivation. Implementation challenges, such as teacher understanding and resource availability, are identified and possible solutions suggested. The implications of this research include recommendations for improving the social studies curriculum in elementary schools and developing training for teachers to implement innovative learning models. This research contributes to further understanding of the effectiveness of the social studies learning model in elementary school and provides a basis for further development in improving the quality of social studies learning at the elementary level.